Economic reforms in France: Bleak macroeconomic data is shaking politics in Paris and cementing France's traditional approach towards the Economic and Monetary Union - Paweł Tokarski (Stiftung Wissenschaft und Politik (SWP), 2014)
With the third government since his election in May 2012, President Hollande will soon enter the second half of his term of office. He came to power with promises of economic recovery. However, the implementation of a coherent economic program quickly became an uphill battle. French voters' persistent dissatisfaction resulted in two sound electoral defeats of the "Parti socialiste" and record support for the "Front National". The difficulties of the second largest Eurozone economy are sooner or later likely to affect the Eurozone's stability. Why is it so hard to reform France? What does President Hollande expect from the Eurozone? And is there an acceptable way to assist French reforms? (SWP Comments)
Keywords: 330